Analisis Jaminan dalam Akad Mudharabah di Perbankan Syariah - Riska Komalasari; Darul Arqom; Fharizal Prakasa Suhaimi; Rasidah Novita Sari (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
This research was conducted with the aim of analyzing the guarantees contained in profit sharing agreements such as mudharabah agreements contained in sharia banking. In this research, a normative approach is used. A normative approach is used to examine the provision of guarantees in production sharing agreements from the perspective of Muamalat jurisprudence. This research shows that profit sharing contracts such as mudarabah essentially have no guarantees, except for guarantees against the possibility of moral hazard on the part of the contracting parties. In practice, Islamic financial institutions, especially Islamic banks, remove mandatory guarantees from the profit sharing agreements they make with their partners (customers). However, keep in mind that the guarantee of absolute rights will only end if the loss arises due to your fault, negligence or breach of contract. If the loss is caused by negligence, or a breach of customer contract, then warranty coverage should not be addressed.